Effects of palm tocotrienols on oxidative stress and bone strength in ovariectomised rats - Nazrun AS,; Khairunnur A,; Norliza M,; Norazlina M,; Ima Nirwana S, (Penerbit UKM, 2008)
Oxidative stress has been associated with postmenopausal osteoporosis which pre-disposes to risk of fracture. Palm tocotrienol is a potent antioxidant and has the poten-tial to be used for treatment of post-menopausal osteoporosis. The aim of the study is to determine if palm tocotrienol supplementation could alleviate oxidative stress in ovariectomised rat model and improve its bone strength. The rats were di-vided into four groups: (i) sham-operated group (SHAM) (ii) ovariectomised-control group (OVX) (iii) ovariectomised and given 60mg/kg α-tocopherol by oral gavage (OVX + ATF) (iv) ovariectomised and given 60mg/kg palm tocotrienols by oral gavage (OVX + PTT). After eight weeks of treatment, blood samples were taken to measure oxida-tive status (MDA, SOD and GPX) while the femurs were biomechanically tested for strength and resistance to fracture. Ovariectomy was shown to induce oxidative stress as shown by the raised MDA levels and reduced GPX activity. Palm tocotrienols seemed to offer protection against the ovariectomy-induced oxidative stress as shown by the suppression of MDA levels and raised GPX and SOD activities in the OVX+PTT group. In comparison, α-tocopherol was only able to raise the SOD but not as high as palm tocotrienols. The biomechanical tests have shown that ovariectomy has not af-fected the bone strength significantly after eight weeks. Palm tocotrienols supplemen-tation for eight weeks was effective in preventing oxidative stress in a post-meno-pausal rat